Conference on civil engineering problems overseas 1968 (Institution of Civil Engineers, 1968)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in 1968.
Keywords: Civil engineering -- Congresses.; elektronické knihy; electronic books